OJ -ALGEBRA OF MEASURABLE ELEMENTS WITH RESPECT TO A SUBADDITIVE MEASURE ON JORDAN ALGEBRAS - Kodirov Komiljon Raximovich; Tukhtasinov Tokhirjon Shokirjon o’g’li (Journal Park Publishing, 2022)
This article proves that the topological Jordan algebra of measurable elements with respect to sub additive measure is an OJ - algebra
Keywords: algebra; trace; functional